Podocyte Endocytosis in Regulating the Glomerular Filtration Barrier - Tian, Xuefei; Bunda, Patricia; Ishibe, Shuta (Frontiers in Medicine, 2022)
Endocytosis is a mechanism that internalizes and recycles plasma membrane components and transmembrane receptors via vesicle formation, which is mediated by clathrin-dependent and clathrin-independent signaling pathways. Podocytes are specialized, terminally differentiated epithelial cells in the kidney, located on the outermost layer of the glomerulus. These cells play an important role in maintaining the integrity of the glomerular filtration barrier in conjunction with the adjacent basement membrane and endothelial cell layers within the glomerulus. An intact podocyte endocytic machinery appears to be necessary for maintaining podocyte function. De novo pathologic human genetic mutations and loss-of-function studies of critical podocyte endocytosis genes in genetically engineered mouse models suggest that this pathway contributes to the pathophysiology of development and progression of proteinuria in chronic kidney disease. Here, we review the mechanism of cellular endocytosis and its regulation in podocyte injury in the context of glomerular diseases. A thorough understanding of podocyte endocytosis may shed novel insights into its biological function in maintaining a functioning filter and offer potential targeted therapeutic strategies for proteinuric glomerular diseases.